Tracheotomy in a tertiary health care unit in Northwestern Mexico: Description and analysis of a series of cases - Lugo Machado, Juan Antonio (2017)
Objective: To describe the conditions and characteristics of the tracheostomy procedure in a tertiary health care unit and analyze its association with the recorded outcome. Materials and methods: A retrospective, observational and descriptive study that included patients operated in the Otorhinolaryngology Unit of the Northwest National Medical Center, Sonora, from August 2014 to August 2015. Fifty-two (52) complete clinical records of consecutive series of cases were reviewed, out of which 57% were men with an average age of 56.2 years old. Descriptive statistics was used to characterize the distribution, and the differences were evaluated by chi-square test and Student’s t-test. Results: Seventy-one percent (71%) of the patients underwent surgery in an operating room and 29% in the ICU. In the latter, more than half of the cases had a tracheostomy (51.92%). Prolonged intubation was the main cause of 51% of the tracheostomy procedures. Complications reached 34.61% of the cases and included the following disorders in descending order: cannula occlusion, peristomal emphysema, hemorrhage, bilateral pneumothorax, decanulation and innominate fistula. These complications were significantly associated with obesity, prolonged endotracheal intubation and general anesthesia. Mortality occurred in 7.69% of the patients. Conclusions: No significant difference was found between complications occurred in an operating room and the ICU. Prolonged mechanical ventilation was the primary indication for tracheotomy. Decannulation was the main cause of complication. Moreover, BMI was a risk factor for complications. The mortality rate was 7.69%, which was more elevated compared to other studies.